Near‐Field Drives Long‐Lived Shallow Trapping of Polymeric C3N4 for Efficient Photocatalytic Hydrogen Evolution. (23rd June 2021) - Wang, Wenchao; Bai, Xueqin; Ci, Qing; Du, Lili; Ren, Xingang; Phillips, David Lee
Abstract: Undesired photoelectronic dormancy through active species decay is adverse to photoactivity enhancement. An insufficient extrinsic driving force leads to ultrafast deep charge trapping and photoactive species depopulation in carbon nitride (g‐C3 N4 ). Excitation of shallow trapping in g‐C3 N4 with long‐lived excited states opens up the possibility of pursuing high‐efficiency photocatalysis. Herein, a near‐field‐assisted model is constructed consisting of an In2 O3 ‐cube/g‐C3 N4 heterojunction associated with ultrafast photodynamic coupling. This In2 O3 ‐cube‐induced near‐field assistance system provides catalytic "hot areas", efficiently enhances the lifetimes of excited states and shallow trapping in g‐C3 N4 and this favors an increased active species density. Optical simulations combined with time‐resolved transient absorption spectroscopy shows there is a built‐in charge transfer and the active species lifetimes are longer in the In2 O3 ‐cube/g‐C3 N4 hybrid. Besides these properties, the estimated overpotential and interfacial kinetics of the In2 O3 ‐cube/g‐C3 N4 hybrid co‐promotes the liquid phase reaction and also helps in boosting the photocatalytic performance. The photocatalytic results exhibit a tremendous improvement (34‐fold) for visible‐light‐driven hydrogen production. Near‐field‐assisted long‐lived active species and the influences of trap states is a novel finding for enhancing (g‐C3 N4 )‐based photocatalytic performance. Abstract : A near‐field‐assisted model containing an In2 O3 ‐cube/g‐C3 N4 heterojunction that can assist with ultrafast photodynamic coupling is constructed. Near‐field assistance is found to enhance long‐lived shallow charge trapping in g‐C3 N4 so as to favor generating an increased photoactive species population. A mechanism for the photophysical and photochemical routes is deduced from time‐resolved spectroscopy combined with results from optical simulations.